Sobrecarga y síntomas depresivos en cuidadores primarios de pacientes en cuidados paliativos domiciliarios - Barrera Robledo, Viviana Eugenia (Universidad Antonio Nariño, 2023)
In our country, care corresponds largely to the family, constituting a fundamental pillar in the provision of care to patients. Despite this, it has little knowledge about the effect of illnesses on caregivers, who commit their lives solving other needs, leading to overloaded by all the activities they perform during that care and having an emotional impact when seeing a family member suffering (1)